2016
DOI: 10.1136/oemed-2015-103005
|View full text |Cite
|
Sign up to set email alerts
|

Environmental factors associated with baseline and serial changes in fractional exhaled nitric oxide (FeNO) in spice mill workers

Abstract: This study suggests that chilli pepper sensitisation is associated with high FeNO (>50 ppb), more strongly compared with garlic, despite the low prevalence of sensitisation to chilli. Elevated inhalant spice dust particulate is associated with a delayed elevation of FeNO across the 24-hour period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…The triglyceride glucose (TyG) index, which is calculated from fasting measurements of triglyceride and glucose, has been suggested as a reliable surrogate marker of IR 6 8 . Previous studies have found that a high baseline TyG index was related to the development of diabetes and coronary atherosclerosis 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…The triglyceride glucose (TyG) index, which is calculated from fasting measurements of triglyceride and glucose, has been suggested as a reliable surrogate marker of IR 6 8 . Previous studies have found that a high baseline TyG index was related to the development of diabetes and coronary atherosclerosis 9 11 .…”
Section: Introductionmentioning
confidence: 99%
“…FeNO tends to increase 24 h after exposure to the allergen and measurement of FeNO is recognized as an accurate, reproducible, and important non-invasive surrogate marker for airway inflammation. There was almost 12% increase within 24 h thus demonstrating a strong association with elevated levels of suspended spice dust [24]. Similarly, in a study conducted in Grenada, occupational exposure and respiratory health problems among nutmeg production workers were observed in Grenada.…”
Section: Exposure Assessmentmentioning
confidence: 88%
“…The ATS/ERS guidelines make evidence based recommendations in the interpretation of FeNO levels and they have been used in African studies (52,53). Elevated FeNO levels greater than 50ppb in adults and greater than 35ppb in children indicate eosinophilic airway in ammation that is suggestive of probable allergic asthma.…”
Section: Lung Function Assessmentmentioning
confidence: 99%